Components of the Co3Cr4(PO4)6-Cr(PO3)3 System and the Compound CoCr2(P2O7)2 as New Ceramic Pigments - Luxová, Jana; Těšitelová, Kateřina; Podzemná, Veronika; Šulcová, Petra; Bosacka, Monika; Blonska-Tabero, Anna; Filipek, Elzbieta (Elsevier Science SA, 2019)
The compounds: Co3Cr4(PO4)6, Cr(PO3)3 and CoCr2(P2O7)2 were tested for possible application as ceramics and anticorrosive pigments. They were characterized by SEM analysis, determination of particle size distribution and thermal stability. All phosphates were thermally stable up to 1100 °C so they can be used for colouring of middle-temperature ceramic glazes. The gravimetrical determination of corrosive loss of steel sheets and other corrosion factors characterizing the resistance to corrosion in an aqueous environment of the phosphates were discussed. The colour properties of the compounds were studied for powders and pigments introduced into organic matrix and several single-firing ceramic glazes. It is shown that the investigated phosphates can be used as ceramic pigments only for leadless single-firing ceramic glaze. The optimum pigment concentration sufficient for colouring glaze was close to 2 wt %. Generally, the examined phosphates have interesting green, greenish-blue and cyan shades.
Složky systému Co3Cr4 (PO4)6-Cr(PO3)3 a sloučenina CoCr2(P2O7)2 jako nový keramický pigment
Keywords: Inorganic pigments; Optical properties; Corrosion; Ceramics; System CoO-P2O5-Cr2O3; CoCr2(P2O7)2; Anorganické pigmenty; optické vlastnosti; koroze; keramika systém CoO-P2O5-Cr2O3; CoCr2(P2O7)2